Circularly Polarized Luminescence from Zero‐Dimensional Hybrid Lead‐Tin Bromide with Near‐Unity Photoluminescence Quantum Yield. Issue 51 (17th November 2022) - Wei, Yi; Li, Chen; Li, Yawen; Luo, Zhishan; Wu, Xiaoyu; Liu, Yulian; Zhang, Liming; He, Xin; Wang, Wei; Quan, Zewei
Abstract: Zero‐dimensional (0D) hybrid metal halides with perfect host‐guest structures are promising candidates to construct circularly polarized luminescence (CPL)‐active materials. However, it still remains challenging to obtain 0D chiral metal halides with simultaneously strong CPL and high photoluminescence quantum yield. Here, a new enantiomeric pair of 0D hybrid lead‐tin bromides, ( RR / SS ‐C6 N2 H16 )2 Pb0.968 Sn0.032 Br6  ⋅ 2H2 O ( R / S ‐PbSnBr ⋅ H2 O), is reported. The R / S ‐PbSnBr ⋅ H2 O compounds not only show intriguing self‐trapped exciton emissions with near‐unity quantum yield, but also present intense CPL with a dissymmetry factor g lum of ±3.0×10 −3 . Such CPL activities originate from the asymmetric [SnBr6 ] 4− luminophores in R / S ‐PbSnBr ⋅ H2 O, due to the induced structural chirality by the organic ligands via N−H⋅⋅⋅Br hydrogen bonds. Furthermore, CPL emissions with tunable colors from R / S ‐PbSnBr ⋅ H2 O and dehydrated compounds are reversibly observed, which extends their chiroptical applications. Abstract : A new enantiomeric pair of 0D hybrid lead‐tin bromides, ( RR / SS ‐C6 N2 H16 )2 Pb0.968 Sn0.032 Br6  ⋅ 2H2 O, shows not only strong self‐trapped exciton emissions with near‐unity photoluminescence quantum yield (PLQY) but also intense circularly polarized luminescence (CPL) signals with a dissymmetry factor g lum of ±3.0×10 −3 .